PENERAPAN TaRL( TEACHING AT THE RIGHT LEVEL) BERBANTUAN MEDIA PICTURE MATCHING GAME UNTUK MENINGKATKAN HASIL BELAJAR PENJUMLAHAN PECAHAN PADA SISWA KELAS V SD - Lukitasari, Yenik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Classroom Action Research (CAR) is motivated by the lack of learning outcomes of fifth grade students of SD Negeri 9 Tambakasri, Malang Regency in learning fractions in mathematics, especially adding fractions with different denominators. The purpose of this study is to improve students' learning outcomes in mathematics, especially adding fractions with different denominators through the application of the TaRL approach assisted by Picture Matching Game media. This study uses a classroom action research (CAR) method which is carried out in 2 cycles, where in each cycle there are 2 meetings. The subjects of this study were 11 fifth grade students of SD Negeri 9 Tambakasri, Malang Regency. The data collection technique used an evaluation test of student learning outcomes. The results of the study showed an increase in learning completeness from 63.6% in cycle I to 81.8% in cycle II. From these data, it can be concluded that the TaRL approach assisted by Picture Matching Game can improve the learning outcomes of fifth grade students of SD Negeri 9 Tambakasri on the material of adding fractions with different denominators.